Victimization of old people as members of a special marginal group - Kostić Miomira P.; Đorđević Radmila (Temida)
In this paper the authors explain the role of the old in status systems both in modern societies and throughout history. The authors point out the role of the ageing process in defining the marginal status of old people and their risks to become victims of abuse. Because of their biological and psychological characteristics and their social status, the old are vulnerable to various forms of abuse: physical, psychological and sexual violence, negligence, and self-negligence, abandonment and economic exploitation. The case study has been done in cooperation with the expert team of Gerontology center of the town Niš.